Penurunan Kecemasan Keluarga Pasien Stroke Dengan Family Centered Empowerment Model - Christina Dewi Prasetyowati; Sri Wahyuni (Jurnal Smart Keperawatan, 2021)
Stroke merupakan keadaan yang terjadi akibat adanya gangguan suplai darah ke otak yang awal timbulnya mendadak, progresi cepat berupa defisit neurologis fokal yang berlangsung 24 jam atau langsung menimbulkan kematian. Dampak dari stroke selain bagi pasien juga menimbulkan dampak psikologis kecemasan bagi keluarga pasien dari ketidaksiapan keluarga dalam merawat pasien stroke. Kecemasan pada keluarga dapat diatasi dengan pemberian edukasi berbasis family centered empowerment model. Penelitian ini bertujuan untuk mengetahui penurunan kecemasan keluarga pasien stroke dengan family centered empowerment model di RSUD Gambiran Kota Kediri. Desain penelitian menggunakan pra experiment dengan rancangan one group pretest and posttest design. Pengambilan sampel secara non probability sampling dengan teknik accidental sampling yang berjumlah 54 orang. Pengumpulan data menggunakan kuesioner kecemasan HARS dan dianalisa dengan uji  Wilcoxon Signed Ranks Test. Hasil menunjukkan nilai p = 0,000 yang artinya ada pengaruh family centered empowerment model terhadap penurunan kecemasan keluarga pasien stroke. Kata Kunci : family centered empowerment model; kecemasan; keluarga; strokeAnxiety Reduction Of  Family Patients With Stroke And Family Empowerment Centered ModelAbstractStroke is a condition that occurs due to disruption of blood supply to the brain which has a sudden onset, rapid progression in the form of a focal neurological deficit that lasts 24 hours or immediately causes death. The impact of stroke in addition to the patient also causes psychological effects of anxiety for the patient's family from the family's unpreparedness in caring for stroke patients. Anxiety in the family can be overcome by providing education based on the family centered empowerment model. This study was aimed to determine the decrease in family anxiety of stroke patients with the family centered empowerment model at Gambiran Hospital, Kediri City. The research design used a pre-experimental design with a one group pretest and posttest design. The Sampling was taken by non-probability sampling with accidental sampling technique, totaling 54 people. Data was collected using the HARS anxiety questionnaire and analyzed using the Wilcoxon Signed Ranks Test. The results showed the value of p = 0.000 which means that there is an effect of family centered empowerment model on reducing family anxiety of stroke patients.Key Word: family centered empowerment model; anxiety; family; stroke